Mitochondria‐Targeted Artificial "Nano‐RBCs" for Amplified Synergistic Cancer Phototherapy by a Single NIR Irradiation. Issue 8 (21st May 2018) - Zhang, Liang; Wang, Dong; Yang, Ke; Sheng, Danli; Tan, Bin; Wang, Zhigang; Ran, Haitao; Yi, Hengjing; Zhong, Yixin; Lin, Han; Chen, Yu
Abstract: Phototherapy has emerged as a novel therapeutic modality for cancer treatment, but its low therapeutic efficacy severely hinders further extensive clinical translation and application. This study reports amplifying the phototherapeutic efficacy by constructing a near‐infrared (NIR)‐responsive multifunctional nanoplatform for synergistic cancer phototherapy by a single NIR irradiation, which can concurrently achieve mitochondria‐targeting phototherapy, synergistic photothermal therapy (PTT)/photodynamic therapy (PDT), self‐sufficient oxygen‐augmented PDT, and multiple‐imaging guidance/monitoring. Perfluorooctyl bromide based nanoliposomes are constructed for oxygen delivery into tumors, performing the functions of red blood cells (RBCs) for oxygen delivery ("Nano‐RBC" nanosystem), which can alleviate the tumor hypoxia and enhance the PDT efficacy. The mitochondria‐targeting performance for enhanced and synergistic PDT/PTT is demonstrated as assisted by nanoliposomes. In particular, these "Nano‐RBCs" can also act as the contrast agents for concurrent computed tomography, photoacoustic, and fluorescence multiple imaging, providing the potential imaging capability for phototherapeutic guidance and monitoring. This provides a novel strategy to achieve high therapeutic efficacy of phototherapy by the rational design of multifunctional nanoplatforms with the unique performances of mitochondria targeting, synergistic PDT/PTT by a single NIR irradiation (808 nm), self‐sufficient oxygen‐augmented PDT, and multiple‐imaging guidance/monitoring. Abstract : A unique near‐infrared‐responsive "Nano‐RBC, " PFOB@LIP‐IR780, is engineered for achieving mitochondria‐targeting phototherapy, amplified synergistic photothermal therapy/photodynamic therapy (PDT) by a single NIR irradiation (808 nm), self‐sufficient oxygen‐augmented PDT and computed tomography, photoacoustic and fluorescence multiple‐imaging guidance/monitoring.